2018
DOI: 10.1159/000487800
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Early Oropharyngeal Dysphagia in Patients with Multiple System Atrophy

Abstract: Background/Aims: Dysphagia, a symptom of multiple system atrophy (MSA), is a major clinical concern. In this study, we investigate the characteristics of early oropharyngeal dysphagia (OD) in patients with MSA, and the differences between MSA subtypes. Methods: Patients enrolled in the study had previously been diagnosed with MSA at the clinic of the Department of Neurology, and had been referred for a videofluoroscopic swallowing study (VFSS), between 2005 and 2014, to check for dysphagia. The clinical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 23 publications
(34 reference statements)
3
34
1
1
Order By: Relevance
“…Petrovic in contrast described a much later onset of dysphagia in MSA-P patients at 9.0 ± 3.7 years (63). A recent study in 59 Korean MSA patients showed a much earlier dysphagia onset in both MSA sub-types (MSA-P: 2.94 ± 1.43 years, MSA-C: 3.05 ±1.24 years) (64).…”
Section: Pharyngeal Findings In Msamentioning
confidence: 99%
“…Petrovic in contrast described a much later onset of dysphagia in MSA-P patients at 9.0 ± 3.7 years (63). A recent study in 59 Korean MSA patients showed a much earlier dysphagia onset in both MSA sub-types (MSA-P: 2.94 ± 1.43 years, MSA-C: 3.05 ±1.24 years) (64).…”
Section: Pharyngeal Findings In Msamentioning
confidence: 99%
“…Dysphagia is defined as an impairment of this complex and integrated sensorimotor system. Neurogenic dysphagia (ND) is typically occurring in patients with neurological disease of different etiologies (see Table 1), and it is associated to high mortality, morbidity, and social costs [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Neurological problems that cause dysphagia can be categorized in many different ways: anatomic location of the lesion (e.g., central nervous system, peripheral nervous system or muscle), pathogenetic mechanism of disease (e.g., ischemic injury or degenerative process), etiology, or clinic presentation (e.g., dementia or movement disorders).…”
Section: Introductionmentioning
confidence: 99%
“…Those with MSA often exhibit symptoms of dysphagia much earlier than those with PD [13]. A previous study on dysphagia in MSA reported that dysphagia was mostly limited to aspiration symptoms in MSA-C, while difficulty in swallowing, increased mealtime, and drooling were frequent in MSA-P [6]. In another study, the latency from the onset of dysphagia symptoms to the onset of dietary modification was 2.3 years in MSA-P and 5.1 years in MSA-C [24].…”
Section: Discussionmentioning
confidence: 97%
“…The type of MSA was determined according to the predominant motor symptoms at the last visit: predominantly parkinsonian (MSA-P) or predominantly cerebellar (MSA-C). If a patient had both parkinsonism and cerebellar dysfunctions with no clear predominance, the patient was designated MSA-PC (also known as MSA-mixed) [4][5][6]. Disease onset was defined as the initial presentation of any motor symptoms, because the onset of autonomic symptoms was unclear in many patients.…”
Section: Patientsmentioning
confidence: 99%